EXPLORING THE POTENTIAL OF ENGLISH FOR SPECIFIC PURPOSES AND EXPERIENTIAL LEARNING IN FOSTERING TOURISM AND HOSPITALITY STUDENTS’ SOFT SKILLS: AN EXPERIENCE REPORT - Vasconcelos, Sandra (PUPIL: International Journal of Teaching, Education and Learning, 2024)
Aiming to contribute towards the ongoing reflection on the potential of experiential learning and how it can enhance students’ employability, this paper focuses on the role English language teaching and learning can play within this scope, outlining a practical example focusing on tourism and hospitality education. Drawing from notes from the field, this experience report describes a set of activities focusing on careers and job applications, which are not only aligned with current market and recruitment trends, but also support the development of key skills such as communication, critical-thinking and creativity. Part of a comprehensive teaching and learning strategy, whose key outputs comprised a digital portfolio and a simulated job interview, these activities are framed by a theoretical rationale taking into account a set of pre-defined learning outcomes and syllabus, as well as the specific application setting and target audience (3rd year students preparing for their work placements/about to conclude their undergraduate degree in tourism). In addition to describing this rationale and the actual strategy, the paper will put forward a fresh and comprehensive outlook on the affordances of experiential learning, paving the way for future work.